Comparative Study of Generalized Sum Graphs via Degree-Based Topological Indices - Muhammad Javaid; Saira Javed; Ebenezer Bonyah (Journal of Mathematics)
In theoretical chemistry, topological indices (TIs) have important role to predict various physical and structural properties of the study under molecular graphs. Among all topological indices, Zagreb-type indices have been used more effectively in the chemical literature. In this paper, we have computed first Zagreb, second Zagreb, forgotten, and hyper Zagreb indices of the generalized Q-sum graph H1QαH2 in the form of different TIs of its basic graphs, where α≥1 is a positive integer. This family of graphs is obtained by the lexicographic product of the graph QαH1 and H2, where QαH1 is constructed with the help of the generalized line superposition operation Qα on H1. As a conclusion, we also checked the correlation between predefined graph H1H2 under the operation of lexicographic product H1 and H2 with newly defined generalized Q-sum graphs H1QαH2 using linear regression models of various degree-based TIs.